A century of pluralistic ignorance: what we have learned about its origins, forms, and consequences - Miller, Dale T. (Frontiers in Social Psychology, 2023)
The concept of pluralistic ignorance was introduced a century ago by social psychologist, Floyd Allport. It has been broadly applied in the social sciences, including psychology, sociology, political science, and economics. Pluralistic ignorance is a situation in which group members systematically misestimate their peers' attitudes, feelings, and private behaviors. This paper reviews the range of phenomena that pluralistic ignorance has been invoked to explain, the different accounts that have been offered for its emergence, and the various techniques that have been employed to dispel it. It distinguishes between micro and macro variants of pluralistic ignorance and discusses the challenges involved in generating a theory that encompasses both variants.